2014
DOI: 10.21608/jpp.2014.55441
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Behavior of Yield, Grain Quality, Stem Borer and Storage Insect Infestation Traits for Some Rice Genotypes at Different Sowing Dates.

Abstract: 2011 and 2012 seasons. The objectives of this investigation is amid to study the genetic behavior of ten rice genotypes under three sowing dates (May1 st , May 15 th and May30 th), the effect of different sowing dates on grain quality characters, and on the infestation by stem borer and to evaluate the susceptibility of certain rice varieties against the infestation by Lesser grain borer, Rhizopertha dominica (F.). The tested genotypes were;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Regarding heritability estimates for all traits under study, the results revealed that the broad-sense heritability was higher than the narrow-sense heritability estimates for all characters. Our results corroborated with El-Malky et al [28], Hammoud et al [29], and El-Malky et al [30]. As a matter of fact, a character or trait influenced by non-additive gene action usually show low genetic advance but high heritability, while for the character under additive gene action, heritability and genetic advance values are always high [49].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding heritability estimates for all traits under study, the results revealed that the broad-sense heritability was higher than the narrow-sense heritability estimates for all characters. Our results corroborated with El-Malky et al [28], Hammoud et al [29], and El-Malky et al [30]. As a matter of fact, a character or trait influenced by non-additive gene action usually show low genetic advance but high heritability, while for the character under additive gene action, heritability and genetic advance values are always high [49].…”
Section: Discussionsupporting
confidence: 92%
“…of primary branches/panicle (PBPP), panicle weight (PW), panicle length (PL), and grain yield/plant (GYPP), respectively. PCA was performed using XLSTAT v19.1 et al [29] and El-Malky et al [30]. The best cross combinations were Giza178ÂSakha101, Giza178ÂGz6903, Giza178ÂGz95771, Giza178ÂGiza175, Sakha101ÂGz6903, Sakha101ÂHassawi, Gz69031ÂGz95771, Gz6903ÂHassawi, Gz6903ÂGiza175, Gz6903ÂSakha103 and Gz9577ÂSakha103.…”
Section: Discussionmentioning
confidence: 99%
“…With delay in sowing, the number of filled grains per panicle decreased significantly. Dawadi and Chaudhary (2013) and El-Malky and El-Zun (2014) found that number of filled grains per panicle increased in the early sowing and declined gradually in the successive later sowing dates.…”
Section: Agronomic Studiesmentioning
confidence: 99%
“…Sowing date of rice affects degree of rice infestation by the rice leafminer and the rice stem borer, which are the most destructive rice pests. The occurrence and prevalence of insect pests are affected by host plant availability, growth stage, sowing and transplanting dates (El-Malky and El-Zun 2014). Due to the insect pests, there was severe damage to the rice grain yield during the different growth stages.…”
Section: Introductionmentioning
confidence: 99%